Dehydroepiandrosterone-induced polycystic ovary syndrome mouse model requires continous treatments to maintain reproductive phenotypes - Haowen Wu; Bining Zhao; Qiyang Yao; Jihong Kang (BMC, 2023)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common endocrinopathy associated with infertility and metabolic disorder in women of reproductive age. Animal models have been developed and used as tools to unravel the pathogenesis of PCOS, among which most postnatal models employ continuing experimental manipulations. However, the persistence and stability of these animals after modeling is unknown. Dehydroepiandrosterone (DHEA)-induced PCOS mouse model is commonly used in PCOS studies. Thus the aim of the present study was to investigate the reproductive features of DHEA-induced PCOS mice fed a normal chow or an high-fat diet (HFD) with treatment withdrawal or consecutive treatments after PCOS mouse models were established. Methods Prepubertal C57BL/6 J mice (age 25 days) were injected (s.c.) daily with DHEA on a normal chow or a 60% HFD for 20 consecutive days to induce PCOS mouse models. Mice injected with the vehicle sesame oil were used as controls. After 20 days, mice were divided into 2 groups, namely "Continue dosing group" and "Stop dosing group". The animals were consecutively treated with DHEA or DHEA + HFD, or housed without any treatment for 2 or 4 weeks. Estrous cycles were evaluated during this period. At the end of the experiment, serum testosterone (T) levels were measured and the morphology of ovaries was evaluated. Results The mice in Continue dosing groups maintained reproductive phenotypes of PCOS mouse models. In contrast, 2 or 4 weeks after PCOS models were established, the mice with treatment withdrawal in Stop dosing groups exhibited normal serum testosterone levels, regular estrous cycle, and relatively normal ovarian morphology. In addition, even with consecutive treatments, there was no marked difference in body weight between DHEA mice on the normal chow or an HFD in Continue dosing groups and the control animals 3 weeks after modeling. Conclusions After PCOS mice were induced with DHEA or DHEA + HFD, the mice still need consecutive treatments to maintain reproductive phenotypes to be regarded as PCOS mice that meet the diagnostic criteria of PCOS defined by the 2003 Rotterdam criteria.